Von Ereignissen zu Strukturen - Pirner, Hans J. (Heidelberger Jahrbücher online, 2020)
A single event is not sufficient, to identify a structure. Only the repetition of similar events can lead to an understanding of the underlying structure. A historical event can never be fully explained by its supposed structure, conversely a structure cannot only be explained by events. In physics, explanation is a necessary condition to understand an event. In this essay, I give examples of structures on various natural scales: In the world around us, we experience matter in solid, liquid or gaseous states, which mirror their structure. At the level of individual atoms, we encounter the slow-down of the thermal dance of the molecules at very low temperature. The elementary particles have intricate family structures that are just as complicated as family structures in anthropology. The universe presents events that can illuminate the long dark night from 1 million years to 1 billion years after the big bang. I show how the researcher inductively derives physical structures from events, but I will also indicate that there are metastructures found by mathematical deduction.
Gesehen am 22.07.2020